2003
DOI: 10.1002/cne.10570
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in N‐acetylaspartylglutamate and the 67 kDa form of glutamic acid decarboxylase immunoreactivities in the visual system of albino and pigmented rats after optic nerve transections

Abstract: This study compares the immunohistochemical distributions of N-acetylaspartylglutamate (NAAG) and the large isoform of the gamma-aminobutyric acid (GABA)-synthesizing enzyme glutamic acid decarboxylase (GAD(67)) in the visual system of albino and pigmented rats. Most retinal ganglion cells and their axons were strongly immunoreactive for NAAG, whereas GAD(67) immunoreactivity was very sparse in these cells and projections. In retinorecipient zones, NAAG and GAD(67) immunoreactivities occurred in distinct popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Consistent with the potential of this transmitter to regulate neurotransmission via activation of presynaptic receptors in these brain regions, putative NAAGergic synapses were observed on the cell bodies and dendrites of PAG neurons, as well as in the neuropil (Figure 1c). While these data alone are insufficient to confirm the synaptic localization of this immunoreactivity, studies with this antibody at the ultrastructural level previously localized NAAG immunoreactivity to synaptic vesicles [30] and optic nerve transection studies demonstrated that NAAG immunoreactivity is associated with NAAG-containing synaptic terminals in various regions of the CNS [31,32]. Additionally, depolarization-induced calcium-dependent NAAG release has been demonstrated repeatedly [10,33].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the potential of this transmitter to regulate neurotransmission via activation of presynaptic receptors in these brain regions, putative NAAGergic synapses were observed on the cell bodies and dendrites of PAG neurons, as well as in the neuropil (Figure 1c). While these data alone are insufficient to confirm the synaptic localization of this immunoreactivity, studies with this antibody at the ultrastructural level previously localized NAAG immunoreactivity to synaptic vesicles [30] and optic nerve transection studies demonstrated that NAAG immunoreactivity is associated with NAAG-containing synaptic terminals in various regions of the CNS [31,32]. Additionally, depolarization-induced calcium-dependent NAAG release has been demonstrated repeatedly [10,33].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the endogenous dipeptide N -acetyl-aspartyl-glutamate (NAAG) selectively activates mGluR3 with an EC 50 of less than 100 μm whilst producing no significant activation of mGluR2 receptors at 1 mm (Wroblewska et al 1997). Furthermore, NAAG is expressed strongly in retinal ganglion cells (Moffett, 2003), is released in the SC C 2006 The Authors. Journal compilation C 2006 The Physiological Society following optic tract stimulation (Tsai et al 1990) and has been proposed to function as a neurotransmitter (Neale et al 2000;Gafurov et al 2001).…”
Section: Modulation Of Inhibitory Responses By Group II Mglursmentioning
confidence: 99%
“…It is thought that the alterations in GABAergic neurotransmission lead to dysregulation of glutamatergic activity, which in turn is responsible in part for the pathophysiology of schizophrenia. NAAG is expressed extensively in interneurons of neocortex in rat (Moffett and Namboodiri 1995), and monkey (Moffett and Namboodiri 2006), and is colocalized with the GABA synthesizing enzyme glutamic acid decarboxylase (Moffett 2003). Because NAAG has been shown to reduce glutamate release (Xi et al.…”
Section: Discussionmentioning
confidence: 99%